Global mental health in low and middle income, especially African countries. (30th August 2016) - Freeman, M.
Abstract : Mental health for all is the main goal of the global mental health movement. Central characteristics to achieving this are examination of the social determinants of health and a more preventive approach; greater task shifting or task sharing; emphasis on common as well as serious mental disorder; a strong research base and a commitment to human rights. Putting the interventions in place in countries with limited resources and particularly African countries that will best promote mental health is challenging and requires a careful balancing of priorities and approaches. Evidence in the form of randomised control trials and cost-effectiveness studies are necessary but not sufficient to achieving the set objectives. This editorial points to various considerations that may contribute towards the quest for mental health for all.